3D numerical study of large-scale two-phase flows with contact lines and application to drop detachment from a horizontal fiber. (April 2018) - Wang, Sheng; Desjardins, Olivier
Highlights: An accurate, conservative, and robust numerical strategy to simulate two-phase flows in complex geometries is presented. This approach combines a conservative level set method to capture the interface, an immersed boundary method to represent the curved boundary, and a curvature boundary method to treat the contact lines. Excellent agreement found with experiments for droplet detachment from a horizontal fiber caused by gravity or surface energy. A critical Etövös number is found for droplet detachment caused by gravity. A critical Weber number is found for droplet detachment caused by cross-flow. Abstract: One fundamental problem in understanding two-phase flows in coalescers is determining how large of a drop can attach to and subsequently remain on a fiber. Droplet detachment can be caused by gravity or shear from the cross-flow overcoming the adhesion between the drop and the fiber. Previous studies have found the critical size of a drop on a hydrophilic fiber under gravity and the critical size of a drop on a hydrophobic fiber. In this paper, we present an accurate, conservative, and robust numerical strategy to simulate large-scale two-phase flows in complex geometries, and validate the capability of the proposed approach to predict the critical size of a drop on a cylindrical hydrophilic fiber under gravity and on a hydrophobic fiber without gravity. Then, an exploratory study of the critical size of a drop on a cylindrical fiber with cross-flow is performed.